2011
DOI: 10.1002/smj.929
|View full text |Cite
|
Sign up to set email alerts
|

When do strategic alliances inhibit innovation by firms? Evidence from patent pools in the global optical disc industry

Abstract: Research and development (R&D) consortia are specialized strategic alliances that shape the direction and scope of firm innovation activities. Little research exists on the performance consequences of participating in R&D consortia. We study the effect of patent pools, a unique form of R&D consortia, on firm performance in innovation. While prior research on alliances generally implies that patent pools enhance firm innovation, our study finds the opposite. Analyzing data on systemic innovation in the global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(73 citation statements)
references
References 96 publications
(101 reference statements)
1
64
1
7
Order By: Relevance
“…This competition externality creates downward pressure on license fees and individual patent holders compete each other down to the limit licensing levels. 10 We have shown that patent pools can elevate the total licensing fees when they are used to shield weak patents form the threat of litigation. However, the elevated licensing fees have no e¢ ciency consequences in the simple model where only the litigation margin is binding.…”
Section: Equation (1) Thus Implicitly De…nes …Rmmentioning
confidence: 96%
See 2 more Smart Citations
“…This competition externality creates downward pressure on license fees and individual patent holders compete each other down to the limit licensing levels. 10 We have shown that patent pools can elevate the total licensing fees when they are used to shield weak patents form the threat of litigation. However, the elevated licensing fees have no e¢ ciency consequences in the simple model where only the litigation margin is binding.…”
Section: Equation (1) Thus Implicitly De…nes …Rmmentioning
confidence: 96%
“…Given …rm j sets f j , …rm i has no incentive to increase its fee as it would trigger litigation against …rm i. Condition (10) ensures that …rms have no incentive to decrease their license fee either. Thus, in a subgame perfect equilibrium, each …rm sets its licensing fee at the level that deters litigation,…”
Section: The Interplay Of the Demand Margin And Litigation Incentivesmentioning
confidence: 99%
See 1 more Smart Citation
“…For DVDs, comparable data on transfer speeds and product launches (Flamm 2013), as well as patents (Joshi and Nerkar 2011) suggest a decline in innovation. For the MPEG-2 standard pool, patenting declines after the creation of a pool, as firms shift away from inventing toward implementing new technologies (Vakili 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We encourage other researchers to use this overview as a repository for further research on the evolution of technology diffusion. Henderson and Cockburn (1996), Pakes and Griliches (1980), Johnson and Popp (2003), Trajtenberg (1990), Ahuja and Katila (2001), Dushnitsky and Lenox (2005), , Joshi andNerkar (2011), Wang and Success with product innovations, i.e., share of sales from products new to the market or alternatively share of sales from products new to the firm. Cockburn et al (2010) Number of patents that led to new product, e.g., for a new drug launch in the pharmaceutical industry.…”
Section: The Role Of Corporate Entrepreneurshipmentioning
confidence: 99%